PRAKTIK POLITIK TRANSAKSIONAL DAN ANTROPOSENTRISME DALAM MENGANALISIS KERUSAKAN LINGKUNGAN AKIBAT PENAMBANGAN EMAS ILEGAL DI KECAMATAN KLUET TENGAH - Julihardiyat, Disky; Sari, Cut Maya Aprita (Journal of Political Sphere, 2025)
PT Beri Mineral Utama (BMU) was granted an iron ore mining permit but operated illegal gold mining in Simpang Tiga Village, Central Kluet, South Aceh. This activity led to environmental damage and water pollution. This research aims to analyze the persistence of illegal gold mining after permit closure and examine indications of transactional politics involved. Using a qualitative descriptive method, data were collected through interviews, observation, and document analysis. The study applies Transactional Politics theory and the concept of Anthropocentrism. Findings reveal that illegal mining persists due to the collusion between mining mafias and state actors, anthropocentric government attitudes, and weak law enforcement. The research offers insights to guide concrete solutions to address environmental degradation.